From Trust to Triumph: What Drives Tourists to Recommend Thailand’s Hidden Cultural Gems? - Mohamed Soliman; Tawat Noipom; Muhammadafeefee Assalihee; Arunneewan Buaniew; Ahmad Albattat (Tourism and Hospitality, 2025)
This study aims to explore the factors influencing word-of-mouth (WOM) intentions among cultural tourists in Thailand’s southern border provinces. This study develops a comprehensive framework predicting WOM intentions by combining the Stimulus–Organism–Response (S-O-R) model, the theory of planned behavior (TPB), and the cognitive–affective–conative (CAC) model, given the critical role of WOM in tourism marketing. Data were collected from 386 cultural tourists through purposive sampling using a self-administered questionnaire. The study employs structural equation modeling (PLS-SEM) to investigate relationships between trust, attitude, satisfaction, and WOM intentions. The findings reveal that trust, satisfaction, and attitude significantly impact WOM intentions. Social influence strongly predicts trust, while the perceived quality of behavior influences attitude. Satisfaction is driven by perceived value, the quality of the experience, the quality of the physical environment, and tourist engagement. This study contributes to cultural tourism literature by integrating different behavioral theories to provide a robust WOM model. This study’s theoretical contributions and practical implications for scholars, policymakers, tourism marketers, and cultural site operators will be further discussed.